A Study of The Concepts of Ira Shor for the Development of Critically Engaged Students in UK Higher Education - Haynes, Lisa (2009)
This study first highlights the urgent needs for the development of critically engaged students in the light of existing crises and unknown future challenges facing society. UK higher education strategy calls for the development of people to generate new ideas and serve democracy, and universities are ideally placed to develop such people. Critical pedagogy is considered as an effective means to draw out the characteristics that define critically engaged students and American professor Ira Shor is identified as a critical educator who has written widely about the subject. Next a literature review is undertaken outlining the evolution of critical pedagogy from its origins in critical theory to its present day contributors, situating Shor amongst them. Then critical contextual analysis is used to explore Shor’s definition of critical pedagogy and three recurrent themes in his writings are identified: a basic contradiction in higher education, dialogical pedagogy, and democratic classrooms. After that there is a brief assessment of his unique contributions. A discussion follows using excerpts from an interview with a British academic and recommendations based on Shor’s concepts for UK higher education are put forward. The study concludes with two of Shor’s self-evaluation questions.